2021
DOI: 10.1177/10790632211024236
|View full text |Cite
|
Sign up to set email alerts
|

Expert Versus Novice: Criminal Expertise in Sexual Burglary and Sexual Robbery

Abstract: Although there has been considerable variation in the application of expertise to offending populations, one aspect that is widely agreed upon is that expertise is best represented on a continuum from novice to expert. The present study, therefore, investigated criminal expertise in 877 hybrid offenses that involve sexual assault and robbery (i.e., sexual robbery) or burglary (i.e., sexual burglary). Specifically, we analyzed the crime-commission processes of both these offenses using latent class analyses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 61 publications
0
16
0
2
Order By: Relevance
“…As Nee (2019) notes, offenders may develop expertise through repeated practice within the same domain, or they may gain more "general" or "overlapping" skills that transfer across similar domains. For example, Reale et al (2021b) found that criminal expertise varies from novice to expert both within and across sexual burglary and sexual robbery domains. Interestingly, both domains had "intermediate" subgroups who shared similar skilled behaviors that were not "specialized" or "domain-specific," but rather, were broadly relevant for interpersonally violent offenses (e.g.…”
Section: Conceptualizing Criminal Expertise In Sexual Offendingmentioning
confidence: 99%
See 4 more Smart Citations
“…As Nee (2019) notes, offenders may develop expertise through repeated practice within the same domain, or they may gain more "general" or "overlapping" skills that transfer across similar domains. For example, Reale et al (2021b) found that criminal expertise varies from novice to expert both within and across sexual burglary and sexual robbery domains. Interestingly, both domains had "intermediate" subgroups who shared similar skilled behaviors that were not "specialized" or "domain-specific," but rather, were broadly relevant for interpersonally violent offenses (e.g.…”
Section: Conceptualizing Criminal Expertise In Sexual Offendingmentioning
confidence: 99%
“…As past studies have had limited success differentiating criminal sophistication between serial and single-incident offenders, a focus on sexual theft offenses may provide a better avenue to capture criminal expertise. Moreover, Reale et al (2021b) found that hybrid sexual theft offenses involve both "specialized" domain-specific skills and more "general" skills related to violent offending. Thus, hybrid offenses can provide a wider range of behavioral indicators of criminal expertise across the crime-commission process.…”
Section: Current Studymentioning
confidence: 99%
See 3 more Smart Citations